Peran Mahasiswa Magang dalam Mendukung Tertib Administrasi dan Pengarsipan Dokumen di Pengadilan Negeri Palangka Raya - Muhammad Ramadhan; Afifah Afifah; Alya Julviana; Annida Auliya; Muhammad Norhadi (Jurnal Kemitraan Masyarakat, 2026)
Legal Skills Practice I (PKH I) is an internship program designed to provide law students with practical experience in understanding the administration, work procedures, and service mechanisms within judicial institutions. This activity was conducted at the Palangka Raya District Court, focusing on administrative management and document archiving as essential components in supporting the judicial process. This article aims to describe the role of internship students in promoting administrative order within the court environment. The method employed consisted of observation and direct participation in administrative activities within the Criminal, Civil, Legal Affairs, and Industrial Relations Court clerk divisions. During the internship, students were involved in document archiving, management of incoming and outgoing correspondence, preparation of official reports, data entry into the Case Tracking Information System (SIPP), and case file management. The results indicate that student participation contributed positively to creating a more organized, systematic, and efficient administrative system. Furthermore, the PKH I program provided valuable practical experience for students in understanding judicial administration, court procedures, and the professional work culture practiced within judicial institutions. These experiences support the development of students’ competencies and readiness to enter the legal profession.